Wood feeding and social living: Draft genome of the subterranean termite Reticulitermes lucifugus (Blattodea; Termitoidae). Issue 2 (21st November 2022) - Martelossi, Jacopo; Forni, Giobbe; Iannello, Mariangela; Savojardo, Castrense; Martelli, Pier Luigi; Casadio, Rita; Mantovani, Barbara; Luchetti, Andrea; Rota‐Stabelli, Omar
Abstract: Termites (Insecta, Blattodea, Termitoidae) are a widespread and diverse group of eusocial insects known for their ability to digest wood matter. Herein, we report the draft genome of the subterranean termite Reticulitermes lucifugus, an economically important species and among the most studied taxa with respect to eusocial organization and mating system. The final assembly (~813 Mb) covered up to 88% of the estimated genome size and, in agreement with the Asexual Queen Succession Mating System, it was found completely homozygous. We predicted 16, 349 highly supported gene models and 42% of repetitive DNA content. Transposable elements of R. lucifugus show similar evolutionary dynamics compared to that of other termites, with two main peaks of activity localized at 25% and 8% of Kimura divergence driven by DNA, LINE and SINE elements. Gene family turnover analyses identified multiple instances of gene duplication associated with R. lucifugus diversification, with significant lineage‐specific gene family expansions related to development, perception and nutrient metabolism pathways. Finally, we analysed P450 and odourant receptor gene repertoires in detail, highlighting the large diversity and dynamical evolutionary history of these proteins in the R. lucifugus genome. This newly assembled genome will provide a valuable resource for further understanding the molecular basis of termites biology as well as for pest control. Abstract : The ~813 Mb long genome of the subterranean termite Reticulitermes lucifugus has been sequenced. Multiple instances of gene duplications were found associated with the R. lucifugus diversification, with lineage‐specific gene families expansions related to development, perception and nutrient metabolism pathways. P450 and odourant receptor genes repertoires display large diversity and a dynamic evolutionary history of these proteins also among other analysed termite genomes.